Analysis and design of a magnetically levitated planar motor with novel multilayer windings - Guo, Liang; Zhang, He; Galea, Michael; Lin, Jing; Lu, Wenqi; Gerada, C. (IEEE, 2015)
This paper proposes a novel permanent magnet planar motor with moving multilayer orthogonal overlapping windings. This novel motor topology can achieve a five-degrees-of-freedom drive using two sets of x-direction windings and two sets of y-direction windings in a coreless configuration. The orthogonal multilayer construction guarantees a high utilization of the magnetic field and realizes decoupling between the x-direction thrust and the y-direction thrust. The topology and operating principle of the planar motor are introduced in this paper. The analytical modeling of the motor is established based on the equivalent current method, and the expressions of forces are derived. The force characteristics of the two-layer and three-layer winding topologies are compared, and the design guidelines of a planar motor are proposed. The analytical and 3-D finite-element model results are validated with the experimental results of a tested prototype.